Multicultural Counseling-a Review of the Literature: Findings and Recommendations - Skafi, Faten Ahmed (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
The importance of multicultural counseling has been widely recognized and discussed. Counselors must be aware of multiple cultures when dealing with multicultural clients. This paper focuses on an in-depth literature review of counseling effectiveness that can be improved by reviewing previous studies that historically analyzed multicultural counseling practices. More specifically, the literature review may frame findings from previous studies examining gaps in multicultural counseling competencies. Most of these studies are based on effectiveness definitions and competencies of cross-cultural counseling. So, this paper highlights the competencies of multicultural counseling in the world, identifying strengths, weaknesses and challenges using a narrative literature review method in order to continue to make meaningful contributions to the profession, bridge gaps and begin to develop a strong competency base for the future of MCC. In addition to some recommendations that deserve further research for future studies.